2015
DOI: 10.2460/ajvr.76.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of directly measured arterial blood pressure at various anatomic locations in anesthetized dogs

Abstract: Results suggested that arterial blood pressures may be dependent on anatomic location and body position. Because this may affect outcomes of studies conducted to validate indirect blood pressure measurement systems, care must be used when developing future studies or interpreting previous results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Several previous studies have also identified discordance between indirect and direct blood pressure measurements taken at different sites (Bodey & Michell, 1996; Rondeau, Mackalonis & Hess, 2013; Acierno et al, 2015). Bodey & Michell (1996) found oscillometric systolic blood pressure measurements were significantly lower at the coccygeal artery compared to the radial artery in standing dogs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several previous studies have also identified discordance between indirect and direct blood pressure measurements taken at different sites (Bodey & Michell, 1996; Rondeau, Mackalonis & Hess, 2013; Acierno et al, 2015). Bodey & Michell (1996) found oscillometric systolic blood pressure measurements were significantly lower at the coccygeal artery compared to the radial artery in standing dogs.…”
Section: Discussionmentioning
confidence: 94%
“…The impact of body position on indirect blood pressure measurement is further highlighted by the results of Rondeau, Mackalonis, and Hess, in which the mean SAP in conscious dogs measured on the forelimb was significantly higher in the sitting position than in lateral recumbency (Rondeau, Mackalonis & Hess, 2013). Finally, significant differences have been noted in direct SAP measurements collected at different anatomic sites, particularly at the carpus and hindlimb (Acierno et al, 2015), suggesting an anatomic basis for discordance in pressures at different sites. Ultimately, the results of these studies underscore the importance of consistency in both measurement site and body positioning when obtaining indirect blood pressure readings, especially when monitoring for the progression of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, individual patient factors can be prioritized when selecting a blood pressure measurement site, the importance of which is underscored by the marked discordance in results in one dog with severe degenerative joint disease in this study. Several previous studies have also identified discordance between indirect and direct blood pressure measurements taken at different sites Rondeau, Mackalonis, & Hess, 2013;Acierno et al, 2015). Bodey and Michell found oscillometric systolic blood pressure measurements were significantly lower at the coccygeal artery compared to the radial artery in standing dogs .…”
Section: Discussionmentioning
confidence: 94%
“…Técnicamente, la presión arterial es la que se obtiene por punción directa de una arteria, usando un transductor de presión conectado a un catéter (Zrimšek et al, 2018); sin embargo, esto requiere sedación o anestesia y, por lo tanto, no es práctico y no refleja la presión real de un paciente despierto, además de ser una técnica compleja e inapropiada para muchas situaciones clínicas (Vachon et al, 2014). Algunos estudios han encontrado que las mediciones de presión arterial de manera invasiva en diversos sitios anatómicos en perros anestesiados pueden variar (Acierno et al, 2015). Un método no invasivo para la medición de la presión arterial es la oscilometría, que consiste en la medición de las pequeñas oscilaciones de la frecuencia cardiaca y el cálculo de la periferia de estas oscilaciones.…”
Section: Introductionunclassified